Reassembling the archives: business history knowledge production from an actor-network perspective. Issue 4 (1st October 2016) - Pfefferman, Talia
Abstract: This paper addresses the dearth of methodological analysis in business history. Questioning the sources of women's marginality in Israeli business history, I integrate a feminist standpoint epistemology with a historically nuanced actor–network theory (ANTi-History) into a critically reflexive methodological account. I claim that this valuable analytical tool elaborates on business historians' craft and offers three main contributions. First, it bolsters the disciplinary rigor of business history and its potential advantages for management and organizational scholarship. Second, the material semiotics of this approach highlights the extent to which nonhuman objects affect power relations in the course of producing a singular historical representation. Third, by tracing the performance of analytical categories such as gender in the course of knowledge production, it delineates the operation of mechanisms of marginality in the past and within the archive. These insights contribute to a better understanding of how business history was rendered masculine.